개체동결 굴(Crassostrea gigas) 복합엑스분의 추출 및 품질특성 - 강진영; 윤재웅; 이소정; 강수태; 김선근; 오광수; Jin-Yeong Kang; Jae-Ung Yun; So-Jeong Lee; Su-Tae Kang; Seon-Geun Kim; Kwang-Soo Oh (농업생명과학연구, 2014)
상품가치를 상실한 장기저장 개체동결 굴로부터 굴소스의 주소재용 엑스분을 추출하기 위한 열수, 잔사 효소분해 및 복합추출조건을 검토하였고, 이들 엑스분들의 품질특성에 대하여 살펴보았다. 추출원료로 사용한 동결저장 18개월째의 개체동결 굴은 부분적으로 프리저번이 일어나 상품가치를 상실한 제품으로 정상 개체동결 굴에 비해 수분 함량은 감소한 반면, VBN 함량은 다소 증가하였다. 특히 TBA 값은 2배 이상 증가하여 지질산화가 장기저장 개체동결 굴의 가장 큰 품질저하 요인이었다. 장기저장 개체동결굴에서 추출한 열수추출, 잔사효소분해 및 이들을 혼합한 복합엑스분(Brix 20°)의 조단백질 및 아미노 질소 함량은 각각 5.5, 8.5 및 6.6%, 281.7, 366.0 및 343.0 mg/100 g으로 잔사효소분해엑스분의 함량이 가장 많았다. 또한 수율은 개체동결 굴 1 kg 당 811, 359 및 1,170 mL로 복합엑스분의 경우 열수 추출엑스분에 비해 약 44%의 추출수율이 증가하였다. 본 복합엑스분은 기존 열수추출엑스분에 비해 이 화학적 성분조성 뿐만 아니라 관능적 품질도 전혀 손색이 없었으며, 굴소스의 주소재로 충분히 사용가능하였다. To develop the effective use of the long term stored individually quick frozen (IQF) oyster Crassostrea gigas, the extraction conditions and food quality characteristics of the taste-active extract from these IQF oysters were investigated. Regarding the chemical compositions, the moisture and volatile basic nitrogen (VBN) contents in the eighteen-months stored IQF oysters (18M-IQFO) with poor quality were 77.9% and 17.9 mg/100 g. In fatty acid composition of total lipid separated from 18M-IQFO, the major fatty acids were 14:0, 16:0, 16:1n-9, 18:1n-9, 18:3n-3, 20:5n-3 and 22:6n-3. During eighteen-month frozen storage, the moisture content and remaining ratio of polyunsaturated fatty acid slightly decreased, but VBN content slightly increased. Three kinds of taste-active extracts, including hot-water extract (HE), scrap enzymatic hydrolysate (EH) and complex extract (CE) from 18M-IQFO were prepared, and examined for quality characteristics of these extracts. The crude protein and amino-N contents in these extracts were 5.5, 8.6 and 6.6%, and 281.7, 366.0 and 343.0 mg/100 g, respectively. And extraction yields in the extracts (Brix 20°) were 811, 359 and 1,170 mL/kg, respectively. The present complex extraction method was superior to the traditional hot-water extraction method in the aspect of yield, amino-nitrogen contents and organoleptic qualities except the odor.